Comparison of Letrozole vs Clomiphene in PCOS Ovulation Induction - Shazia Aftab, Saira Jamshed, Rabia Shahid, Farah Khan, Ayesha Khalid, Mehwish Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder in women of reproductive age and is a major cause of anovulatory infertility. Ovulation induction is the mainstay of therapy, and traditionally, Clomiphene citrate is the first-line agent. Nevertheless, issues about its anti-estrogenic properties on endometrium and cervical mucus have created growing interest in the use of Letrozole as an option. Objective: To compare the effectiveness of Letrozole and Clomiphene citrate in ovulation induction among women with PCOS. Methods: This comparative analysis was implemented between January 2022 and January 2023 and involved 82 women with PCOS attending a Tertiary Care Hospital in Karachi. The participants were also split into two equal groups with half given letrozole and other half given clomiphene citrate. Transvaginal ultrasonography was used to monitor ovulation and the results such as ovulation rate, endometrial thickness, pregnancy rate and adverse effects were noted. The analysis was done with SPSS version 25 and a p-value of less than 0.05 was taken as statistically significant. Results: The ovulation rate was significantly higher in the letrozole group compared to the clomiphene group (73.2% vs 58.5%, p=0.04). Endometrial thickness was also significantly greater with letrozole (9.1 ± 1.3 mm vs 7.4 ± 1.5 mm, p<0.001). The pregnancy rate was higher in the letrozole group (31.7% vs 19.5%, p=0.03). Clomiphene was associated with a higher number of mature follicles and increased incidence of side effects. Conclusion: Letrozole is more effective than clomiphene citrate for ovulation induction in women with PCOS, demonstrating higher ovulation and pregnancy rates with better endometrial response and fewer adverse effects. It should be considered as a preferred first-line agent in the management of PCOS-related infertility. Keywords: Polycystic Ovary Syndrome, Letrozole, Clomiphene Citrate, Ovulation Induction, Infertility, Endometrial Thickness